PARENTING SELF-EFFICACY DAN EMOTION COACHING PADA IBU DENGAN ANAK USIA PRASEKOLAH - Dyah Ayu Rahmawati; Niken Fitri Palupi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Emotional development during the preschool years serves as an essential foundation for children's future self-regulation and social competence. One parenting practice that supports emotional development is emotion coaching, which refers to parents’ ability to recognize, accept, and guide children’s emotions constructively. A factor presumed to influence the implementation of emotion coaching is parenting self-efficacy, defined as parents’ belief in their ability to perform parenting tasks effectively. This study aimed to examine the relationship between parenting self-efficacy and emotion coaching among mothers of preschool-aged children. A quantitative correlational design was employed involving 290 mothers with preschool-aged children. Data were collected using the Self-Efficacy for Parenting Task Index (SEPTI) to measure parenting self-efficacy and the emotion coaching subscale of the Maternal Emotional Styles Questionnaire (MESQ) to assess emotion coaching. Data were analyzed using Spearman Rank correlation. The findings revealed no significant relationship between parenting self-efficacy and emotion coaching (p = 0.135; p > 0.05). These results indicate that mothers’ confidence in their parenting abilities is not directly associated with the application of emotion coaching strategies. The findings suggest that other factors, such as emotional knowledge, parenting experiences, child characteristics, and social support, may play a more substantial role in shaping emotion coaching practices among mothers of preschool-aged children. This study contributes to the understanding of factors influencing parental emotional socialization and highlights the need for further research exploring variables beyond parenting self-efficacy. ABSTRAK Perkembangan emosi pada masa prasekolah merupakan fondasi penting bagi kemampuan regulasi diri dan kompetensi sosial anak pada tahap perkembangan berikutnya. Salah satu praktik pengasuhan yang mendukung perkembangan emosi anak adalah emotion coaching, yaitu kemampuan orang tua dalam mengenali, menerima, dan membimbing emosi anak secara konstruktif. Faktor yang diduga berperan dalam penerapan emotion coaching adalah parenting self-efficacy, yaitu keyakinan orang tua terhadap kemampuannya dalam menjalankan tugas pengasuhan. Penelitian ini bertujuan untuk mengetahui hubungan antara parenting self-efficacy dan emotion coaching pada ibu yang memiliki anak usia prasekolah. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional yang melibatkan 290 ibu yang memiliki anak usia prasekolah. Data dikumpulkan menggunakan Self-Efficacy for Parenting Task Index (SEPTI) untuk mengukur parenting self-efficacy dan subskala emotion coaching dari Maternal Emotional Styles Questionnaire (MESQ) untuk mengukur emotion coaching. Analisis data dilakukan menggunakan korelasi Spearman Rank. Hasil penelitian menunjukkan bahwa tidak terdapat hubungan yang signifikan antara parenting self-efficacy dan emotion coaching (p = 0,135; p > 0,05). Temuan ini mengindikasikan bahwa keyakinan ibu terhadap kemampuan pengasuhan yang dimilikinya tidak secara langsung berkaitan dengan penerapan strategi emotion coaching. Hasil penelitian menunjukkan kemungkinan adanya faktor-faktor lain, seperti pengetahuan tentang emosi, pengalaman pengasuhan, karakteristik anak, maupun dukungan sosial, yang lebih berperan dalam menentukan praktik emotion coaching pada ibu yang memiliki anak usia prasekolah.